Longitudinal evaluation and treatment compliance of patients with mood disorders treated with electroconvulsive therapy - Begüm Aygen Gümüş; Hülya Ertekin (SERNEV, 2021)
Introduction: The aim of this research was to evaluate the demographic characteristics, diagnosis, treatment compliance and follow-up of outpatient clinic patients who had undergone electroconvulsive therapy for the treatment of mood disorders.Methods: This retrospective study has been conducted based on inpatient and outpatient clinical records of mood disorders patients who were treated with ECT between 2015-2018 in Department of Psychiatry Faculty of Medicine in University of Onsekiz Mart, Çanakkale Turkey.Results: The distribution of study population were classified as bipolar disorder patients [50% (n=5) in manic episode, 30% (n=3) in depressive episode, and 20% (n=2) in mixed episode] and 35% (n=7) of the depressive disorder patients had depression with psychotic symptoms, 60% (n=12) had depression without psychotic symptoms, and 5% (n=1) had catatonic depression. During the evaluation for the reasons of electroconvulsive therapy, the need for rapid response was most important requirement in depression patients, and agitation excitation treatment was most important requirement in bipolar disease patients. During follow-up 55% (n=11) of the depression patients continued their outpatient visits regularly after discharge, and the mean follow-up period was 14.10 months while 70% (n=7) of the bipolar disease patients had continued their outpatient visits regularly after discharge. The mean follow-up period was 11 months.Conclusion: Electroconvulsive therapy may be an important factor that increases treatment compliance for patients with mood disorders.Keywords: bipolar disorder, depression, mood disorder, electroconvulsive therapy, treatment compliance